Preclinical characterization of an mRNA-encoded anti-Claudin 18.2 antibody - Hayat Bähr-Mahmud; Ursula Ellinghaus; Christiane R. Stadler; Leyla Fischer; Claudia Lindemann; Anuhar Chaturvedi; Jan Diekmann; Stefan Wöll; Imke Biermann; Bernhard Hebich; Caroline Scharf; Manuela Siefke; et al. (OncoImmunology)
IMAB362/Zolbetuximab, a first-in-class IgG1 antibody directed against the cancer-associated gastric-lineage marker CLDN18.2, has recently been reported to have met its primary endpoint in two phase 3 trials as a first-line treatment in combination with standard of care chemotherapy in CLDN18.2-positive Her2 negative advanced gastric cancer. Here we characterize the preclinical pharmacology of BNT141, a nucleoside-modified RNA therapeutic encoding the sequence of IMAB362/Zolbetuximab, formulated in lipid nanoparticles (LNP) for liver uptake. We show that the mRNA-encoded antibody displays a stable pharmacokinetic profile in preclinical animal models, mediates CLDN18.2-restricted cytotoxicity comparable to IMAB362 recombinant protein and inhibits human tumor xenograft growth in immunocompromised mice. BNT141 administration did not perpetrate mortality, clinical signs of toxicity, or gastric pathology in animal studies. A phase 1/2 clinical trial with BNT141 mRNA-LNP has been initiated in advanced CLDN18.2-expressing solid cancers (NCT04683939).